Ebook literário interativo em inglês para crianças - Oliveira, Ana Beatriz Caddah de (2022)
The need for communication in global context has made English language essential. Along with digital media, they are part of a dominating reality that is increasingly inserted into people's routine. Printed books are falling into disuse and getting children's attention to English language teaching through them has become even more challenging. Searching for more interactive resources, with sounds, videos, movements and technological tools is currently almost indispensable in order to capture the interest of this last generation. With that in mind, the present work aims to create an interactive ebook, whose objective is to assist in the acquisition / learning of the English language through digital technology, which also results in student’s entertainment and encouragement towards reading by the use of playfulness, story, creativity and interactivity inserted in it.